Sociological analysis of remote work as a new format of current population employment in Russia - E. O. Zapoleva; A. A. Simonova; V. V. Pit (Цифровая социология)
The article discusses remote work as a subject of scientific research, describes the factors stimulating the development of distance employment and substantiates the need for a sociological study of this phenomenon in view of the high potential for the impact of changes in forms of employment not only on the labor market, but also on other social structures. Sociologists extremely rarely consider the remote work, despite the increased relevance in recent years, as a subject of study. Scientific publications devoted to remote work as the main type of employment, as a rule, relate to personnel management issues. However, it should be noted that changes in the structure of employment can also affect other social institutions, processes and relationships: the institution of the family, domestic relations, social and professional communications, social mobility, and the very relationship of a person to work. The authors have conducted preliminary monitoring of the media and blogosphere in the Tyumen region and come to the conclusion that, as of today, the applied research methods do not allow to fully reveal the impact of remote employment on all spheres of social life and describe the trends. Therefore, an in-depth sociological analysis of telecommuting with the help of in-depth interviews, interviews with experts, questionnaires to specialists employed in the labor market and representatives of the authorities is required to identify trends, prospects and social consequences.